A RARE CASE OF MYXEDEMA COMA IN A CRITICALLY ILL PATIENT WITH SEPTIC SHOCK: A CASE REPORT - Tolentino, Kurt Bryan; Gagelonia, Janelle; Agonoy, Adrian Kevin; Cabral , Monica Therese (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Myxedema coma is a rare and life-threatening disorder of hypothyroidism occurring in 0.22 per 1 million people per year diagnosed clinically. We report an 87-year-old female, known to have non-ischemic dilated cardiomyopathy, and COPD, presenting with a 2-day history of colds progressing to desaturations at room air. At the ER, was only responsive to vigorous tapping, without spontaneous movement of extremities and eye-opening prompting intubation. At the ER, capillary blood glucose was unreadably low, and hypotensive hence started on vasopressors and inotropes. Laboratory tests showed hyponatremia (129 meqs/L), elevated Creatinine (1.3 mg/dl), an elevated TSH (56.61 uIU/ml), and low FT4 (0.29 ng/dl) and FT3 (1.00 pg/ml). We started loading doses of Levothyroxine per orem and per rectum and Liothyronine, as IV Levothyroxine was not available, however, succumbed to her disease on the 1st day of admission. Prompt treatment and recognition of myxedema coma should be done to prevent mortality in this rare disorder.